Kinetics of a Tuberculosis-Specific Gamma Interferon Release Assay in Military Personnel with a Positive Tuberculin Skin Test - van Brummelen, Sigrid E. (American Society for Microbiology (ASM), 2010)
Treatment of latent Mycobacterium tuberculosis infection on the basis of the tuberculin skin test (TST) result is inaccurate due to the false-positive TST results that occur after Mycobacterium bovis BCG vaccination or exposure to nontuberculous mycobacteria (NTM). Gamma interferon release assays (IGRAs) are based on M. tuberculosis-specific antigens. In a previous study among BCG-naïve military employees, a positive TST result after deployment was mostly associated with a negative IGRA result, suggesting exposure to NTM. Data regarding the kinetics of IGRAs are limited and controversial. The present study aimed to reassess the rate of false-positive TST results and to evaluate the kinetics of the Quantiferon TB Gold In-Tube assay (QFT-Git) in military personnel with a positive TST result. QFT-Git was performed at the time of inclusion in the study and was repeated after 2, 6, 12, and 18 or 24 months. Of 192 participants, 17 were recruits and 175 were screened after deployment (n = 169) or because of travel or health care work. Baseline positive QFT-Git results were observed in 7/17 (41.2%) and 12/174 (6.9%) participants, respectively. During follow-up, a negative QFT-Git result remained negative in 163/165 (98.8%) participants. Of 18 subjects with an initial positive QFT-Git result, reversion to a negative result occurred in 1/6 (16%) recruits, whereas it occurred in 8/12 (66%) subjects after deployment or with other risk factors (P = 0.046). The quantitative result was significantly lower in subjects with reversion than in those with consistent positive results (P = 0.017). This study confirmed a low rate of positive QFT-Git results among military personnel with a positive TST result after deployment, supporting the hypothesis of exposure to NTM. Reversion of the majority of initially low-positive QFT-Git results indicates that QFT-Git may be useful for the diagnosis of later reinfections.